Utilización de bloques nutricionales con adición de subproductos de cosecha (alfalfa, harina de hoja de nopal y desechos de mercado), empleados en la alimentación de Cuyes Criollos (cavia porcellus) en la fase de crecimiento y engorde. - Gómez Calvopiña, Blanca Rebeca (2020)
The objective of this research project was to evaluate the effect of blocks with the addition of harvest by-products (alfalfa, nopal leaf meal and market waste), used in feeding guinea pigs (Cavia porcellus) in the growth and fattening phase; evaluating: Feed consumption, weight gain, feed conversion and profitability, net benefits. A completely randomized design with three treatments was used, 5 experimental units per treatment, 60 observations for 4 weeks: T1 = Alfalfa flour nutritional block, T2 = Nopal flour nutritional block, T3 = Market waste nutritional block. In the food consumption variable, the highest consumption was determined in T1 with an average of 133,20 g per week. The highest weight increase was presented by T1 with an average of 888,49 g. The best feed conversion reached T3, with an average of 2,75. The best marginal rate of return was presented in T1, with 27%.